A literature review on the impact of disasters on healthcare systems, the role of nursing in disaster management, and strategies for cancer care delivery in disaster-affected populations - Wang, Wen; Li, Hui; Huang, Miao (Frontiers in Oncology, 2023)
The impact of disasters on healthcare systems and populations is profound, and the prevalence of blood tumors in disaster-affected populations is a significant concern. Nurses play a crucial role in disaster management and response, particularly in addressing the challenges and opportunities related to tumor care. This review article focuses on the healthcare delivery challenges and opportunities related to disaster nursing and blood tumor care. It begins by emphasizing the importance of nursing in disaster management and the prevalence of blood tumors in disaster-affected populations. The article then delves into the role of nurses in disaster preparedness, response, and recovery, including the challenges and opportunities that arise in providing cancer care in disaster settings. The review also highlights case studies and successful examples of nursing interventions in disaster settings and tumor management. Finally, it offers recommendations for future research and practice in disaster nursing and blood tumor care. In summary, this review article underscores the critical role of nurses in disaster management and response, particularly in addressing the challenges related to blood tumor care. It provides insights into the current state of disaster nursing and tumor care and offers recommendations for advancing research and practice in this important field.